Sexually Dimorphic Impact of Chromium Accumulation on Human Placental Oxidative Stress and Apoptosis. (23rd October 2017) - Banu, Sakhila K; Stanley, Jone A; Taylor, Robert J; Sivakumar, Kirthiram K; Arosh, Joe A; Zeng, Lixia; Pennathur, Subramaniam; Padmanabhan, Vasantha
Abstract: Environmental contamination with hexavalent chromium (CrVI) is a growing problem both in the United States and developing countries. Hexavalent chromium is widely used in numerous industries. Environmental exposure to CrVI adversely affects pregnancy outcomes and subsequent health of 2 generations, resulting in higher pregnancy loss, spontaneous abortion and low birth rate. Pregnant women exposed to CrVI through occupational settings experience increased risk of spontaneous abortion, stillbirth, preterm birth, and neonatal death. Children of the CrVI exposed women experience respiratory problems, perinatal jaundice, and increased birth defects. Because placental dysfunction may have a role in such adverse pregnancy outcome, we tested the hypothesis that environmental Cr exposure in pregnant women results in Cr accumulation in the human placenta, which could increase placental oxidative stress by disrupting antioxidant machinery and inducing apoptosis . Studies using frozen, deidentified human term placenta samples indicated that: (1) Cr accumulates in human term placenta tissues and (2) increase in Cr accumulation is positively correlated with oxidative stress and apoptotic markers, and altered antioxidants levels. Interestingly, there was a sexual dimorphism in the correlation between Cr accumulation and oxidative stress, and expression of apoptotic and antioxidant markers. Mechanistic in vitro studies using human trophoblast cells BeWo confirmed the detrimental effects of Cr in altering antioxidant genes. For the first time, this study provides evidence in support of a positive correlation between Cr accumulation in the human placenta and accelerated oxidative stress, with a gender bias toward the male sex.